Farms, Fertiliser, and Financial Frictions : Yields from a DSGE Model - Walker, Sebastien (IMF Working Papers; Working Paper, 2017)
This paper develops a Dynamic Stochastic General Equilibrium (DSGE) model with a financial accelerator which captures key features of low-income countries (LICs). The predominance of supply shocks in LICs poses distinct challenges for policymakers, given the negative correlation between inflation and the output gap in the case of supply shocks. Our results suggest that: (1) in the face of a supply-side shock, the most desirable interest rate rule involves simply targeting current inflation and smoothing the policy interest rate; and (2) ignoring financial frictions when evaluating policy rules can be particularly problematic in LICs, where financial frictions loom especially large.